Predictors of treatment outcome in patients with paediatric onset multiple sclerosis. (July 2020) - Kopp, Tine Iskov; Blinkenberg, Morten; Chalmer, Thor Ameri; Petersen, Thor; Ravnborg, Mads Henrik; Soelberg Sørensen, Per; Magyari, Melinda
Background: Disease-modifying therapies (DMT) are increasingly used for children with multiple sclerosis (MS) even though most double-blinded randomized controlled trials evaluating efficacy, safety and dosing strategy of a specific drug have included adults. Objective: To investigate predictors of treatment outcomes in patients with paediatric onset MS treated with DMTs. Methods: Prospective cohort study from the nationwide Danish Multiple Sclerosis Registry including all patients with a MS diagnosis who initiated treatment with an approved DMT before the age of 18 ( N  = 137) and followed until their 25th birthday. Selected baseline predictors were tested in univariate and multivariate regression models. Results: Multivariate analyses showed that being female and having disease duration for 2 or more years prior to DMT initiation predicted a higher relapse rate. In addition, disease duration and baseline expanded disability status scale (EDSS) predicted both confirmed disability worsening and improvement. We found no difference in treatment outcome between children with MS onset before and after the age of 13 years. Conclusions: The efficacy of DMT in paediatric onset MS patients is comparable to that seen in adult onset MS patients. Earlier treatment start is associated with a beneficial prognosis in the paediatric cohort.